2016
DOI: 10.4103/1319-2442.182400
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of living kidney donors after donation: A report from Cote d′Ivoire

Abstract: Kidney transplantation from living kidney donors (LKDs) because of its good results represents a good option for the treatment of patients with the end-stage renal disease. Kidney donation is a relatively safe procedure according to several studies. We conducted this cross-sectional study in order to describe the demographic, clinical, and renal outcome of LKD in Côte d'Ivoire. From March to November 2014, LKD residing in Côte d'Ivoire at the time of investigation and having donated the kidney more than one ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This result contrasts with a study carried out in Côte d'Ivoire as a prelude to the kidney transplantation project, which identified a large number of potential living donors [17]. To increase the number of effective donors, accurate information and promotion of donation is needed, for, a study carried out in Côte d'Ivoire on the future of the living donors has shown that the risk related to kidney donation is weak after an average of 4 years follow-up [18] as reported in the literature. However, one should note that kidney disease patients are sometimes reluctant to ask for renal donation from a living person.…”
Section: Discussionmentioning
confidence: 88%
“…This result contrasts with a study carried out in Côte d'Ivoire as a prelude to the kidney transplantation project, which identified a large number of potential living donors [17]. To increase the number of effective donors, accurate information and promotion of donation is needed, for, a study carried out in Côte d'Ivoire on the future of the living donors has shown that the risk related to kidney donation is weak after an average of 4 years follow-up [18] as reported in the literature. However, one should note that kidney disease patients are sometimes reluctant to ask for renal donation from a living person.…”
Section: Discussionmentioning
confidence: 88%
“…Only 14 living kidney donors were included; 3 complained residual pain and 5 living kidney donors had regular nephrological follow up. Significant proteinuria was noted in 7 LKD, and 6 LKD had GFR<60mL/min [18].…”
Section: Impact Of Renal Donation On Physical Healthmentioning
confidence: 95%
“…Ivory Coast implemented the law authorizing organ donation in 2012 [43] and between 2013 and 2015, ten living-related kidney transplantations had been done [44].…”
Section: West Africamentioning
confidence: 99%